Fermentation And Purification Of Lipase By Burkholderia Metallica Using Column Reactor - Ezzreen Zafhrina Mohamad Redza, Nur (Pusat Pengajian Teknologi Industri, 2020)
In this work, fermentation was conducted for the feedstock and purification of lipase by Burkholderia metallica using a column reactor. The targeted parameter for this research such as salt stability, types and concentrations of polyethylene glycol(PEG) and salt, pH of extraction solution and flowrate ml/s to see the performance of extractive purification system. Aqueous impregnated resin system(AIRS) is applied using porous glass beads grafted with polyethylene glycol (PEG). An evaluation studies on AIRS were performed with various molecular weight of polyethylene glycol (PEG) (PEG 2,000, PEG 4,000, PEG 6,000) and different type of salts (sodium citrate, potassium citrate and sodium acetate) as phase component. Liquid extractant of PEG was immobilized on the inert support (porous glass beads) and correspond to the aqueous state phase to surmount the drawback of aqueous two phase extraction (ATPE). The technique combines liquid-liquid extraction with ease if operation of column chromatography.